Phenotypic and Genotypic Characterization of Novel Polyvalent Bacteriophages With Potent In Vitro Activity Against an International Collection of Genetically Diverse Staphylococcus aureus - Whittard, Elliot; Redfern, James; Xia, Guoqing; Millard, Andrew; Ragupathy, Roobinidevi; Malic, Sladjana; Enright, Mark C. (Frontiers in Cellular and Infection Microbiology, 2021)
Phage therapy recently passed a key milestone with success of the first regulated clinical trial using systemic administration. In this single-arm non-comparative safety study, phages were administered intravenously to patients with invasive Staphylococcus aureus infections with no adverse reactions reported. Here, we examined features of 78 lytic S. aureus phages, most of which were propagated using a S. carnosus host modified to be broadly susceptible to staphylococcal phage infection. Use of this host eliminates the threat of contamination with staphylococcal prophage — the main vector of S. aureus horizontal gene transfer. We determined the host range of these phages against an international collection of 185 S. aureus isolates with 56 different multilocus sequence types that included multiple representatives of all epidemic MRSA and MSSA clonal complexes. Forty of our 78 phages were able to infect > 90% of study isolates, 15 were able to infect > 95%, and two could infect all 184 clinical isolates, but not a phage-resistant mutant generated in a previous study. We selected the 10 phages with the widest host range for in vitro characterization by planktonic culture time-kill analysis against four isolates:- modified S. carnosus strain TM300H, methicillin-sensitive isolates D329 and 15981, and MRSA isolate 252. Six of these 10 phages were able to rapidly kill, reducing cell numbers of at least three isolates. The four best-performing phages, in this assay, were further shown to be highly effective in reducing 48 h biofilms on polystyrene formed by eight ST22 and eight ST36 MRSA isolates. Genomes of 22 of the widest host-range phages showed they belonged to the Twortvirinae subfamily of the order Caudovirales in three main groups corresponding to Silviavirus, and two distinct groups of Kayvirus. These genomes assembled as single-linear dsDNAs with an average length of 140 kb and a GC content of c. 30%. Phages that could infect > 96% of S. aureus isolates were found in all three groups, and these have great potential as therapeutic candidates if, in future studies, they can be formulated to maximize their efficacy and eliminate emergence of phage resistance by using appropriate combinations.